Implementation of Knowledge Management and Human Capital in Micro, Small and Medium Enterprises - Fajar Rezeki Ananda Lubis (Universitas Dharma Wacana, 2022)
Any organization's success is contingent upon the activities of its staff. This results in ongoing changes in human capital management, where knowledge is viewed as critical for developing appropriate responses to market changes and uncertainties. This study will examine the theoretical underpinnings of knowledge management in the Micro, Small, and Medium-Sized Enterprises (MSME) sector from this vantage point. This research focuses on the importance of knowledge in business, human capital management, and knowledge management for MSME players in order to accomplish this goal. The methodology utilized is qualitative in nature and entails a review of theory and literature to establish a determined viewpoint on problems pertinent to the research object. The findings indicate that human capital management is frequently informal, resulting in an insufficient understanding by MSME actors of the importance or low value of their workforce, which is treated as an operator or manual worker rather than as a subject, thereby underestimating them by failing to recognize that they possess the necessary knowledge to strengthen their creativity and innovate in response to competitive demands. We argue that this technique violates fundamental knowledge management principles, most notably adaptability, self-confidence, leadership, and human resource development, all of which contribute to business-to-market uncertainty.